Peran Opsen Pajak Kendaraan Bermotor, Dalam Meningkatkan Pendapatan Daerah, Di Samsat Kota Sukabumi - Muhammad Angga Saputra; Ismet Ismatullah; Risma Nurmilah (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the role of the Additional Collection (Opsen) of Motor Vehicle Tax in enhancing regional revenue at the Samsat Office of Sukabumi City. Utilizing a qualitative case study approach with data collected through interviews, observation, and document analysis, the research reveals that Samsat has actively implemented educational strategies to improve taxpayers' understanding of Opsen PKB, though limitations in resources and media diversification remain challenges. Findings indicate that Opsen PKB significantly boosts taxpayer compliance and contributes substantially to local revenue growth, with compliance rates increasing from 76.3% to 84.2% between 2022 and 2024. Key success factors include transparent fund utilization, digitalized payment systems, and enhanced service quality. Additionally, the study highlights a positive correlation between improved infrastructure funded by Opsen PKB and increased taxpayer willingness to pay. Nonetheless, challenges such as database limitations, inter-agency coordination gaps, and taxpayer object mobility persist. The research emphasizes the importance of institutional strengthening, system modernization, and integrated communication strategies to further optimize tax collection. These findings offer practical recommendations for improving regional fiscal independence and provide a theoretical contribution to local taxation studies.